Pengaruh Olahraga Futsal terhadap Kemampuan Kardiovaskular Siswa di SMAN 4 Kota Bengkulu - Desrio Windoro; Ajis Sumantri (Educative Sportive, 2026)
This study aims to examine the effect of futsal on the cardiovascular capacity of high school students. Futsal was chosen as the research subject because it is an intense physical activity and involves a lot of body movements that can increase heart and lung capacity. This study used a comparative design with a sample of 25 students divided into two groups: a group that regularly participates in futsal training and a group that does not engage in futsal activities. Cardiovascular capacity was measured using a VO2 Max test before and after a 6-week futsal training period. The analysis results showed a significant difference in the improvement of cardiovascular capacity between the group involved in futsal and the control group. These findings provide an important contribution to the development of exercise programs that can support the improvement of heart and lung health for students.